Landscape fire monitoring in the Ukrainian part of the Olmany-Perebrody Transboundary Ramsar site based on remote sensing data - Zibtsev, S. V.; Soshenskyi, O. M.; Myroniuk, V. V.; Gumeniuk, V. V. (Forestry and Forest Melioration, 2019)
Introduction Western Polissia forests play an important role in supporting stability in ecosystems and water balance of the region and the whole Dnieper basin. Currently, up to 400 thousand hectares of Scots pine forests in Ukraine are being dying back affected by pests and diseases, which brings about accumulation of natural combustible materials and, as a result, bigger fires. It is reported that in the territory of Ukraine weather conditions changes will negatively impact fire safety. These are increase of air temperature, shift of seasons, increase of duration of vegetative and fire periods, increase of recurrence and intensity of heat waves and natural hydrometeorological phenomena, and change in local water flow. In Ukraine there is a tendency towards increase of the number of big fires and heavy crown fires that are difficult to extinguish. In addition to climate change and the socio-economic crisis, the situation with fire protection in forests has worsened due to a number of reasons, namely large areas of agricultural lands with crop residues burning, imperfect forestry legislation, insufficient funding, outdated firefighting services, lack of experience and training of firefighters to extinguish big fires, etc. All that points at the necessity to study the flammability of the nature reserve fund territories, in particular the Ukrainian part of the Olmany-Perebrody Trasboundary Ramsar Territory and further to work out an integrated system of wildfire prevention and extinguishing. The aim of the research was to identify time and space distribution of landscape fires and learn the reasons for them to occur which will enable improving the system of natural landscape fire protection. Materials and Methods Due to the lack of reliable geographical data on fires, Earth's remote sensing data remains the only available information source. Using the data on thermal anomalies for the studied area, we obtained information on fire cases recorded by MODIS sensors during 2006-2016. We analyzed a fire history for the area taking into account all landscape fires, namely forest, agricultural and peat ones, pastures burning, etc. The Earth remote sensing methods and data were used in the study. Results Forest fires in the Ukrainian part of the Olmany-Perebrody Transboundary Ramsar site, where the Rivne Nature Reserve is located, is one of the main causes of damage and loss of forests. However, this fact is not given in the official data on fire cases. Thus, according to the official figures of the Reserve, from 2009 to 2019 there were only 3 forest fires. In order to obtain more accurate data, we collected information on the fires that occurred in the Ukrainian part of the transboundary Ramsar territory by means of remote sensing methods. According to the received data, 33 fires were recorded in the studied area during 2006–2016. The multi-year tendency indicates an increase in the number of fires from 1–5 per year during 2006–2012 to 5–8 fires per year during 2014–2016. The largest number of landscape fires occurred in April-May and August-October, which is characteristic of both the region and Ukrainian Polissia, in general. The spring fire peak is caused by the accumulation of a large amount of combustible materials in the previous year (dead and living ground cover) and their rapid drying brought about by spring air temperature rise. Arid conditions which traditionally occur in July-August (high temperature, low humidity) and agricultural fields (straw burning, dry weeds, and stubble burning) cause the summer-autumn fire peak. Even with presence of combustible materials, a fire can only occur under certain circumstances, such as weather conditions and sources of fire. In the study area, the sources are primarily related to human activity, namely dry grass burning in the spring and visitors’ careless handling of forest fire. An analysis of the fires, as well as communication with local experts showed that the fires occurred due to both human negligence and intentional arsons. Thus, the inhabitants of the settlements of Stare Selo, Perehodychi and Drozdyn burn pastures and crop residues in the gardens and fields. Some of these fires go beyond private areas and turn into forest fires. Most of the fires that occurred on the boundary of the reserve lands in September and October are caused by fire brought from neighboring lands and started by private landowners, utilities or state-owned enterprises. Some fires that occurred in areas with high wetlands, a lack of paved roads, and remoteness of settlements and firefighters’ location, are mostly caused by careless handling of fire or arson. The most often cause of intentional arson is local conflicts over how to visit the territory of the reserve. Conclusions To conclude, the problem of landscape fires in the Omany-Perebrody Transboundary Ramsar site is greater than that it is shown in official reports. Moreover, the level of fire risk still increases. Therefore, in order to prevent fires in the territory of the Rivne Nature Reserve which occur due to the population’s actions, it is necessary to resolve local conflicts and explain to the local community how dangerous for flora, fauna and the state in general natural fires are. In order to improve the system of protection of the natural territories in the Rivne Nature Reserve, and in the Ukrainian part of the Omany-Perebrody Transboundary Ramsar site in particular, the recommendations given in this paper should be followed. 5 Figs., 6 Refs.